Value Chain: A Theory or a Tool for Sustainable Development? - Dhakal, Krishna; Shrestha, Anu Joshi (Journal of Innovation in Academia, 2025)
This study explores whether the value chain (VC) is primarily a theory or a practical tool for sustainable development. Using the qualitative analytical approach based on thematic analysis of academic literature, institutional reports, and purposively selected global cases between 2010 and 2025, enabling cross-comparative analysis of environmental, social, and governance (ESG) dimensions shaping VC as tools for sustainable development. The findings indicate that VCs operate as practical instruments for achieving sustainable development rather than solely economic models or just a theory. Evidence across global cases shows consistent improvements in income generation, social inclusion, environmental performance, and governance coordination when VCs are formally structured and supported. This study offers a unified framework that demonstrates how VCs can drive inclusive, resilient, and sustainable development, offering strategic insights for practitioners, policymakers, and industry actors for designing inclusive and climate-resilient interventions following the triple bottom line theory and the concept of circular economy.